Human capital and urbanization in the People's Republic of China - Chunbing Xing (Asian Development Bank Institute (ADBI), 2016)
The relationship between human capital development and urbanization in the People's Republic of China (PRC) is explored, highlighting the institutional factors of the hukou system and decentralized fiscal system. Educated workers disproportionately reside in urban areas and in large cities, and the returns to education are significantly higher in urban areas relative to those in rural areas, and in large, educated cities relative to small, less-educated cities. In addition, the external returns to education in urban areas are at least comparable to the magnitude of private returns. Rural areas are the major reservoir for urban population growth, and the more educated have a higher chance of moving to cities and obtaining urban hukou. Relaxing the hukou restriction, increasing education levels of rural residents, providing training for rural-urban migrants, and guaranteeing equal opportunity for all residents are necessary for a sustainable urbanization process in the PRC. In terms of health, rural-urban migration is selective in that healthy rural residents choose to migrate. Occupational choices and living conditions are detrimental to migrants' health, however. While migration has a positive effect on migrant children, its effect on "left-behind" children is unclear.
Keywords: J24; I12; R23; 330; Human capital; health; education; development; hukou system; urbanization